DE NOVO AND THERAPY-RELATED MYELODYSPLASTIC SYNDROMES: ANALOGIES AND DIFFERENCES - Prof. Giuseppe Leone; Emiliano Fabiani; Maria Teresa Voso (Mediterranean Journal of Hematology and Infectious Diseases)
The aim of our review has been to give an appropriate idea of analogies and differences between primitive MDS (p-MDS) and t-MDS throughout an accurate reviewing of English peer-reviewed literature focusing on clinical, cytogenetic, epigenetic, and somatic mutation features of these two groups of diseases.